(untitled) (Revista Contexto & Educação, 2023)
This study sought to understand that situations of symbolic violence are experienced by blind students in the daily life of the classroom / regular school? For this, we conducted a qualitative research, ethnographic type and for data collection, we used semi-structured interview and systematic observation. The research subjects were eight blind students from six regular schools of the municipal public network and twenty teachers who work in the classes where these students are inserted. The results show that violence in / of the school is expressed in inaccessibility, both regarding the physical-architectural dimension and the programmatic, communicational methodological, technological, among others. And with regard to the teaching / learning process, the educational institution usually attributes the difficulties of students with disabilities, their sensory, intellectual and other disorders and never to an inappropriate teaching practice or mediation, since the routines and School rituals are still tied to the standard student stereotype, which does not match the diversity of students entering schools.